2016
DOI: 10.5114/ceji.2016.65140
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of signaling pathways associated with innate antibacterial immunity in patients with pancreatic cancer

Abstract: Disorders of innate antibacterial response are of fundamental importance in the development of gastrointestinal cancers, including pancreatic cancer. Multi-regulatory properties of the Toll-like receptors (TLRs) (e.g., regulation of proliferation, the activity of NF-κB, gene transcription of apoptosis proteins, regulation of angiogenesis, HIF-1α protein expression) are used in experimental studies to better understand the pathogenesis of pancreatic cancer, for early diagnosis, and for more effective therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 182 publications
(168 reference statements)
0
3
0
Order By: Relevance
“…Although beyond the scope of this review, we would like to point out that as critical regulators of adaptive immunity, innate immunity, and inflammation ( 1 4 ), TRAF proteins may indirectly contribute to the development, progression, and metastasis of various cancers by affecting tumor surveillance, tumor immunity, chronic inflammation and the tumor microenvironment. For example, disorders of innate antibacterial response are of fundamental importance in the development of gastrointestinal cancers, including pancreatic cancer, and increased expression of TRAF6, TLR4, and NOD1 are detected in peripheral blood leukocytes of pancreatic cancer patients ( 337 ). Specific deletion of TRAF3 from myeloid cells leads to development of B lymphomas and liver cancer in mice ( 56 , 174 ).…”
Section: Indirect Mechanisms Of Trafs In Human Cancersmentioning
confidence: 99%
“…Although beyond the scope of this review, we would like to point out that as critical regulators of adaptive immunity, innate immunity, and inflammation ( 1 4 ), TRAF proteins may indirectly contribute to the development, progression, and metastasis of various cancers by affecting tumor surveillance, tumor immunity, chronic inflammation and the tumor microenvironment. For example, disorders of innate antibacterial response are of fundamental importance in the development of gastrointestinal cancers, including pancreatic cancer, and increased expression of TRAF6, TLR4, and NOD1 are detected in peripheral blood leukocytes of pancreatic cancer patients ( 337 ). Specific deletion of TRAF3 from myeloid cells leads to development of B lymphomas and liver cancer in mice ( 56 , 174 ).…”
Section: Indirect Mechanisms Of Trafs In Human Cancersmentioning
confidence: 99%
“…Reportedly, the activation of TLR2 and TLR6 receptors by synthetic lipopeptide significantly reduces tumor growth in mice [ 37 ]. Moreover, intratumoral injection of a toll-like receptor 2/6 agonist has been reported to reduce pancreatic tumor proliferation and metastasis [ 12 , 38 ]. The present study revealed that TLR6 exerted a protective role in the pathogenesis and progression of colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, TLRs are expressed in various normal epithelial and cancer cells. Moreover, previous studies have shown that TLRs are widely implicated in gut inflammation in colitis-associated cancers, as well as in the development of CRC [ [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%